Mr. and Mrs. Bunny-- detectives extraordinaire! [compact disc, unabridged] - Horvath, Polly (Listening Library, 2012)
Middle-schooler Madeline's hippie parents have been kidnapped from Hornby Island, Canada, by foxes, and Madeline, upon discovering that she can understand animal languages, hires two rabbit detectives to find them.